The level of masculinity and feminity and patterns of self-disclosure to male and female friends of UPV freshmen students - Arceo, Daniel Keith M
This study sought to find out the level of Masculinity and Femininity of freshmen students, their patterns of self-disclosure in terms of gender and if there is a relationship between the two mentioned variables. Forty (40)male and forty (40)female freshmen students (SY 2002-2002) and at the same time staying in the dormitories were randomly selected as participants for this study. A modified Masculinity and Femininity Test based on the masculinity and femininity traits given in the undergraduate thesis of Maranon (1992) and a modified self - disclosure test by Miller, Berg and Archer (1983) were utilized for data gathering., It was found in the study that among the forty male respondents, 52.5% scored high in the masculinity items while 47.5% scored high in the femininity items. While the female respondents showed a big difference wherein 70% of them scored high in the femininity items and only 25% of them scored high in the masculinity items. On the other hand, five percent of the female respondents were bound to be androgynous. Patterns of self-disclosure showed that three fourths (3/4) of the male and female respondents prefer to self-disclose to their same sex and only one fourth of them would self-disclose more to their opposite sex or to both male and female friends. The results revealed that there is a significant correlation between the following relationships: a.)Males' masculinity level and their self-disclosure to male friend; b.)Males' masculinity level and their self-disclosure to female friend; c.)Females' femininity level and their self-disclosure to male friend; f.)Females' femininity level and their self-dsclosure to male friend. However, based on a t-critical 0.0304, the following have shown weak relationship with each other. It is difficult to conclude that the level of masculinity and femininity generally affects the pattern of self-disclosure of UPV freshmen students. It was also found in the study that the following significant relationship with each other: a.)Females' masculinity level and their self-disclosure to female friend; b.)Females' masculinity level and their self-disclosure to male friend.